Contribution of Tamarix aphylla to soil organic matter evolution in a natural semi-desert area in Tunisia. (January 2022) - Tambone, Fulvia; Trombino, Luca; Masseroli, Anna; Zilio, Massimo; Pepè Sciarria, Tommy; Daffonchio, Daniele; Borin, Sara; Marasco, Ramona; Cherif, Ameur; Adani, Fabrizio
Abstract: A soil, classified as Arenosol (Eutri-Aridic Arenosol (Calcaric)), located in Neffatia (Tunisia) and populated by the shrub tamarisk ( Tamarix aphylla ), was studied to assess how the litter deriving from tamarisk can affect its characteristics. Several parameters were considered: particle size distributions (PSD), pH, cation exchange capacity (CEC), total CaCO3 content, total nitrogen (TKN), phosphorus and total organic carbon (TOC). Down the soil profile the pH increased from 7.83 to 8.32 as a probable consequence of salts accumulation deriving from the mineralization of the organic matter and the limited leaching due to low rainfall. As expected, TOC and TKN decreased, from the top downwards, and the two parameters were well correlated (TOC vs TKN: R 2 = 0.98; p < 0.05; n = 3). CEC assumed progressively lower values reflecting the decreasing organic matter content (CEC vs TOC: R 2 = 0.93; p < 0.05; n = 3). PSD showed that the presence of roots influenced the quantity of fine particles down the profile and the PSD cumulative curves were indicative of an aeolian origin for the soil parent material, confirming the hypothesis that tamarisk interacts with the environment, trapping sediment and forming the so-called phytogenic dunes. By chemical and spectroscopic analyses, it was possible to assess that tamarisk plant residues directly contributed to the soil organic matter (SOM) accumulation and characteristics. Stable SOM (ligno-humic fraction) closely resembles that of the plant (leaves and stems) and is chemically lacking in the more easily degradable organic components such as fats, hemicellulose, cellulose and proteins. 13 C CPMAS NMR spectroscopy showed that the so-called soil ligno-humic fraction consists of aromatic molecules such as tannins, and aliphatic carbon (i.e. cutins and suberins) already present in the plant and preserved by mineralization processes because they are the most resistant to biological degradation. Graphical abstract: Image 1 Highlights: The contribution to SOM of Tamarix spp. residues was studied in a dryland. In drylands natural vegetation plays a key role in SOM accumulation. Tamarix spp. residues (litter) are rich in aromatic and aliphatic carbon. The so called soil ligno-humic fraction directly derives from the litter.